2016
DOI: 10.3390/toxins8120377
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Microorganisms Inhibit Epithelial Cell Internalization of Botulinum Neurotoxin Serotype A

Abstract: Botulinum neurotoxins (BoNTs) are some of the most poisonous natural toxins known to man and are threats to public health and safety. Previous work from our laboratory showed that both BoNT serotype A complex and holotoxin can bind and transit through the intestinal epithelia to disseminate in the blood. The timing of BoNT/A toxin internalization was shown to be comparable in both the Caco-2 in vitro cell culture and in the oral mouse intoxication models. Probiotic microorganisms have been extensively studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Moreover, SEM also showed that the US-made bacteria showed greater ability to adhere to IEC-6 cells. Considering that the non-specific binding of probiotic bacteria to cell wall constituents has been recently hypothesized as a potential mechanism underlying the ability of probiotics to block the accessibility of pathogen agents ( 37 ), the differences we have observed between the two bacterial formulations, although they require further investigation, appear intriguing.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, SEM also showed that the US-made bacteria showed greater ability to adhere to IEC-6 cells. Considering that the non-specific binding of probiotic bacteria to cell wall constituents has been recently hypothesized as a potential mechanism underlying the ability of probiotics to block the accessibility of pathogen agents ( 37 ), the differences we have observed between the two bacterial formulations, although they require further investigation, appear intriguing.…”
Section: Discussionmentioning
confidence: 85%
“…Non-toxigenic strains of C. butyricum have been used as probiotics to modulate the intestinal ecosystem [75] and suppress experimental colitis in mice [74]. Several different probiotic strains have also shown promising potential for directly blocking the epithelial internalization of botulinum neurotoxin type A in vitro, including Saccharomyces boulardii, Lactobacillus acidophilus, Lactobacillus rhamnosus LGG, and Lactobacillus reuteri [76]. Recently, the probiotic strain of Lactobacillus reuteri was used after antitoxin administration at a therapeutic dose of 1 × 10 9 bacteria daily for a case of infant botulism [77].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Therefore, there are two potential therapeutic pathways to block BoNT intoxication: (1) blocking binding/translocation at the intestinal epithelium/ target cells and (2) degradation or inactivation of the toxin It has been shown that pre-treatment with probiotics (Saccharomyces cerevisiae var. boulardii, Lactobacillus acidophilus, Lactobacillus rhamnosus LGG, and Lactobacillus reuteri) was able to block toxin binding to cells in an in vitro Caco-2 cell culture model and that the mechanism most likely used by the probiotics was steric hindrance of binding to host receptors [96].…”
Section: Probiotics and Inhibition Of Bacterial Toxinsmentioning
confidence: 97%